2007
DOI: 10.1097/mnm.0b013e328155d154
|View full text |Cite
|
Sign up to set email alerts
|

A novel iterative method for lesion delineation and volumetric quantification with FDG PET

Abstract: Based on an iterative procedure, the RTL method has been shown to provide optimal threshold levels independent of the SBR and to be applicable in phantom and in patient studies. It is a promising tool for lesion delineation and volumetric quantification of PET lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 26 publications
3
90
0
1
Order By: Relevance
“…However, MTV in the present study was determined using an essentially fully automated delineation algorithm. Although several viable automated algorithms have been published (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), in many institutions MTV is presently still determined by manual delineation. Manual delineation is known to be prone to intraand interobserver variability as well as to potentially gross size and background-dependent bias if fixed absolute or relative thresholds are used.…”
Section: Discussionmentioning
confidence: 99%
“…However, MTV in the present study was determined using an essentially fully automated delineation algorithm. Although several viable automated algorithms have been published (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), in many institutions MTV is presently still determined by manual delineation. Manual delineation is known to be prone to intraand interobserver variability as well as to potentially gross size and background-dependent bias if fixed absolute or relative thresholds are used.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical model that van Dalen et al (27) derived obtained a background subtracted relative threshold method which is independent of the source to‐background ratio but dependent on the sphere size, and suggested a threshold level >50% for spheres of diameter <12.15emmm. Biehl et al (16) found that appropriate threshold for PET‐GTV delineation is highly dependent on tumor size, and arrived at optimum threshold ranges of about 42%±2% for tumors measuring less than 3 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Van Dalen et al [37] proposed a novel iterative method for tumor delineation and volumetric quantification with FDG-PET using background-subtracted relativethreshold level (RTL). The method is based on a convolution of the point-spread function and a sphere with a certain diameter.…”
Section: Iterative Thresholding Methodsmentioning
confidence: 99%